EKSPATRIAT DAN INDUSTRI LINTAS NEGARA - Al Musadieq, Mochammad (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
This research aims to describe demography characteristics and shock culture of expatriate being assigned in Malang and Surabaya. The research analysis toward 30 respondents by using table of frequency distribution resulted that majority of respondents are representative, age between 30 to 40 years old, Japanese, bachelor, male, married, have kids, accompanied by their kids, first overseas assignment, and stay in Indonesia for 1 to 2 years. Moreover the research shows that majority of respondents are able to cope with cultural differences. They do not have shock culture problems.